Edukasi Lingkungan Anak Sekolah Dasar melalui Petualangan Jelajah Alam di Desa Cingebul - Fernando, Frendi; Azizah, Nadya Rizky; Hidayat, Mohamad Syarif; Urohmah, Annisa; Mu'ajizin, Mohamad Kholis; Nabila, Annisa Alivia; Rahsanindya, Hartika Esti; Baedah, Jaeny Nur; Lia, Ceci; Amelia, Ria; Salsabila, Alfi; Hilda, Nurul (Amirul Bangun Bangsa, 2025)
Environmental education for elementary school children is a crucial intervention for sustainable development. This community service program aims to improve understanding of ecosystems, strengthen awareness of maintaining cleanliness, and foster environmental awareness among elementary school students in Cingebul Village, considering that they are at the concrete operational cognitive development stage that enables conceptual understanding through direct experience. The method used is an experiential learning approach through the